2014
DOI: 10.4103/0976-9668.127300
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of factors related to apoptosis and cellular proliferation in relation to inflammation in dentigerous and odontogenic keratocyst

Abstract: Background:The effect of inflammation on pathogenesis and biological behavior of odontogenic keratocyst (OKC) and dentigerous cyst (DC) is not completely understood. Hence, we aimed to analyze the effect of inflammation on biological behavior of OKC and DC using a proliferative and anti-apoptotic marker, i.e., proliferative cellular nuclear antigen (PCNA) and Bcl-2, respectively.Materials and Methods:Immunohistochemical staining was performed using anti-PCNA and Bcl-2 antibody in 10 cases each of classical OKC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Regarding Bcl-2 and Bax expressions, all cases evaluated showed some degree of immunoreactivity to these proteins. This finding was also observed by different studies that investigated the imbalance in cellular apoptosis in different tumors ( 15 - 17 ). We observed that Bcl-2 was similarly expressed in AOTs and AMBs, with a score of 2 (moderate) in most of the analyzed cases.…”
Section: Discussionsupporting
confidence: 80%
“…Regarding Bcl-2 and Bax expressions, all cases evaluated showed some degree of immunoreactivity to these proteins. This finding was also observed by different studies that investigated the imbalance in cellular apoptosis in different tumors ( 15 - 17 ). We observed that Bcl-2 was similarly expressed in AOTs and AMBs, with a score of 2 (moderate) in most of the analyzed cases.…”
Section: Discussionsupporting
confidence: 80%
“…Four different tumors based on aggressiveness of their clinical behavior were studied in this study. The aggressive behavior of OKC was close to ameloblastoma as in many studies which investigated the expression of markers such as p53, p63, Ki67, PCNA, AgNors and Ipo (20)(21)(22)(23) and concluded that the proteins expressed on epithelial cells of OKC is more alike to that of ameloblastoma than DC.…”
Section: Discussionmentioning
confidence: 78%
“…Particularly, they showed that while PCNA was markedly increased, Bcl-2 was significantly markedly in odontogenic keratocyst and dentigerous cyst. 18 In a different study comprising p53, Bcl-2 and Bax proteins, while expression of p53 and Bcl-2 was found to be positively correlated, expression of p53 and Bax protein was found to be negatively correlated. 19 In line with these findings, in tissues of odontogenic cysts, we also identified significant genetic alterations in genes significantly involved in the formation and progression of human cancers.…”
Section: Discussionmentioning
confidence: 93%
“…Also, both Ki-67 and p53 expressions were advanced in odontogenic keratocyst than dentigerous cyst, suggesting Ki-67 and p53 protein expression might be useful prognostic biomarker in odontogenic lesions. Sreedhar et al 18 also established the expression status of PCNA and BCL-2 proteins in odontogenic keratocyst and dentigerous cyst. Particularly, they showed that while PCNA was markedly increased, Bcl-2 was significantly markedly in odontogenic keratocyst and dentigerous cyst.…”
Section: Discussionmentioning
confidence: 99%